2019
DOI: 10.4103/psychiatry.indianjpsychiatry_526_18
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality disorders in obsessive-compulsive disorder

Abstract: Personality disorders are a common comorbidity in obsessive-compulsive disorder (OCD). The effect of comorbidity on the symptom presentation, course, and treatment outcome of OCD is being discussed here. OCD and obsessive-compulsive personality disorder (OCPD) though similar in their symptom presentation, are distinct constructs. Schizotypal disorder, OCPD, and two or more comorbid personality disorders have been found to be consistently associated with a poor course of illness and treatment response. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…Comorbid personality disorders have been consistently associated with a poor illness outcome and scarce treatment response. 30 In particular, borderline personality disorder has been previously proposed as part of a wider obsessive-compulsive spectrum of disorders. Within the obsessive-compulsive spectrum of disorders, each disorder may be located on a continuum of different conditions on the basis of specific symptom dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbid personality disorders have been consistently associated with a poor illness outcome and scarce treatment response. 30 In particular, borderline personality disorder has been previously proposed as part of a wider obsessive-compulsive spectrum of disorders. Within the obsessive-compulsive spectrum of disorders, each disorder may be located on a continuum of different conditions on the basis of specific symptom dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the psychiatric comorbidities with personality disorders were more frequently associated to the worsened stage. Comorbid personality disorders have been consistently associated with a poor illness outcome and scarce treatment response 30 . In particular, borderline personality disorder has been previously proposed as part of a wider obsessive–compulsive spectrum of disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, she was diagnosed with personality disorder not otherwise specified (F60.9). Among other personality disorders diagnosed in patients with OCD are borderline (5%), avoidant (5-15%), and dependent (7.6%) [9,10].…”
Section: Komentarzmentioning
confidence: 99%
“…Among other personality disorders diagnosed in patients with OCD are borderline (5%), avoidant (5-15%), and dependent (7.6%) [ 9 , 10 ].…”
Section: Commentmentioning
confidence: 99%
“…Fifteen review articles were selected as relevant. 5,[11][12][13][14][15][16][17][18][19][20][21][22][23][24] Ten articles were rejected because they did not meet the search criteria (articles on subclinical OCS). Additionally, 25 original research articles were identified after reference cross-checking and from the 15 selected relevant review articles.…”
Section: Articles Identifiedmentioning
confidence: 99%